2018
DOI: 10.1002/smll.201703277
|View full text |Cite
|
Sign up to set email alerts
|

Faster Electron Injection and More Active Sites for Efficient Photocatalytic H2 Evolution in g‐C3N4/MoS2 Hybrid

Abstract: Herein, the structural effect of MoS as a cocatalyst of photocatalytic H generation activity of g-C N under visible light irradiation is studied. By using single-particle photoluminescence (PL) and femtosecond time-resolved transient absorption spectroscopies, charge transfer kinetics between g-C N and two kinds of nanostructured MoS (nanodot and monolayer) are systematically investigated. Single-particle PL results show the emission of g-C N is quenched by MoS nanodots more effectively than MoS monolayers. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(104 citation statements)
references
References 53 publications
9
86
0
Order By: Relevance
“…Compared with the single g‐C 3 N 4 , the survey XPS spectrum of Mn 0.67 Co 1.33 P/g‐C 3 N 4 sample in Figure a presents obvious binding energy peaks of P, Co, and Mn in addition to C and N elements, which implies the formation of Mn 0.67 Co 1.33 P/g‐C 3 N 4 composite. The C 1s XPS spectrum of g‐C 3 N 4 sample in Figure b can been divided into three peaks, where the one at 284.6 eV is due to the carbon of characteristic graphite phase carbon atoms (C—C) and the other two peaks at 286.8 and 287.2 eV should derive from the aromatic carbon of sp 2 hybrid (N—C═N) and carbon atoms in C—NH 2 or C—(N) 3 groups, respectively . For Mn 0.67 Co 1.33 P/g‐C 3 N 4 sample, the C 1s XPS spectrum in Figure b shifts to the high binding energy direction, which may result from the modification of Mn 0.67 Co 1.33 P on g‐C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the single g‐C 3 N 4 , the survey XPS spectrum of Mn 0.67 Co 1.33 P/g‐C 3 N 4 sample in Figure a presents obvious binding energy peaks of P, Co, and Mn in addition to C and N elements, which implies the formation of Mn 0.67 Co 1.33 P/g‐C 3 N 4 composite. The C 1s XPS spectrum of g‐C 3 N 4 sample in Figure b can been divided into three peaks, where the one at 284.6 eV is due to the carbon of characteristic graphite phase carbon atoms (C—C) and the other two peaks at 286.8 and 287.2 eV should derive from the aromatic carbon of sp 2 hybrid (N—C═N) and carbon atoms in C—NH 2 or C—(N) 3 groups, respectively . For Mn 0.67 Co 1.33 P/g‐C 3 N 4 sample, the C 1s XPS spectrum in Figure b shifts to the high binding energy direction, which may result from the modification of Mn 0.67 Co 1.33 P on g‐C 3 N 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a new peak from HO−C=O groups appears at 289.5 eV in 3D C/g‐C 3 N 4 ‐3 composite . In addition, the fitting peak (288.2 eV) in the C 1s spectrum slightly shifts toward the lower binding energy by 0.3 eV in comparison with that of bulk g‐C 3 N 4 , implying a strong interaction between g‐C 3 N 4 and 3D carbon . Figure c displays the O 1 s high resolution spectrum in different samples, the bulk g‐C 3 N 4 shows two deconvoluted peaks located at 533.1 eV and 532.1 eV which are assigned to absorbed H 2 O, and C‐OH, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…For CNNS and Co 3 S 4 /CNNS, in the range of 780-1,800 cm À1 , the broad adsorption bands represent s-triazine ring units and heptazine heterocyclic ring units [29,32]. The adsorption bands at 2,950-3,710 cm À1 are the OAH bands and residual NAH components, which correspond to uncondensed amino groups and surface-adsorbed H 2 O [9,17]. It can be observed that all nanocomposites have a small peak between 2,300 and 3,400 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…Noble metals including Pt and Ru are efficient cocatalysts, but are restricted by the high cost [7,8]. Therefore, the development of high-efficiency cocatalysts, which are inexpensive and easy to synthesize, is of great significance for achieving efficient, large-scale photocatalytic H 2 evolution [8][9][10]. Among them, metal sulfides (Co 3 S 4 ) as promising cocatalysts have attracted more and more attention, however, they tend to form large particles during the synthesis and have poor dispersibility [11][12][13].…”
Section: Introductionmentioning
confidence: 99%